Effects of a Health‐Partner Intervention on Cardiovascular Risk. Issue 10 (October 2016) - Al Mheid, Ibhar; Kelli, Heval Mohamed; Ko, Yi‐An; Hammadah, Muhammad; Ahmed, Hina; Hayek, Salim; Vaccarino, Viola; Ziegler, Thomas R.; Gibson, Greg; Lampl, Michelle; Alexander, R. Wayne; Brigham, Ken; et al.
Abstract : Background: Lifestyle modifications are first‐line measures for cardiovascular disease prevention. Whether lifestyle intervention also preserves cardiovascular health is less clear. Our study examined the role of a Health Partner–administered lifestyle intervention on metrics of ideal cardiovascular health. Methods and Results: A total of 711 university employees (48±11 years; 66% women, 72% Caucasian/22.5% African Americans) enrolled in a program that promoted healthier lifestyles at Emory University (Atlanta, GA). Anthropometric, laboratory, and physical activity measurements were performed at baseline and at 6 months, 1 year, and 2 years of follow‐up. Results were utilized by the Health Partner to generate a personalized plan aimed at meeting ideal health metrics. Compared to baseline, at each of the 6‐month, 1‐year, and 2‐year follow‐up visits, systolic blood pressure was lower by 3.6, 4.6, and 3.3 mm Hg ( P <0.001), total cholesterol decreased by 5.3, 6.5, and 6.4 mg/dL ( P <0.001), body mass index declined by 0.33, 0.45, and 0.38 kg/m 2 ( P <0.001), and the percentage of smokers decreased by 1.3%, 3.5%, and 3.5% ( P <0.01), respectively. Changes were greater in those with greater abnormalities at baseline. Finally, the American Heart Association "Life's Simple 7" ideal cardiovascular health score increased by 0.28, 0.40, and 0.33 at 6 month, 1 year, and 2 years, respectively, compared to baseline visit. Conclusions: A personalized, goal‐directed Health Partner intervention significantly improved the cardiometabolic risk profile and metrics of cardiovascular health. These effects were evident at 6 months following enrollment and were sustained for 2 years. Whether the Health Partner intervention improves long‐term morbidity and mortality and is cost‐effective needs further investigation.